Letter : Jesus and Julian Hickman Urrutia - Gondra, Angel de
027-0014-001 Euzkadi Ordezkaritza BASQUE DELEGATION. 14, ECCLESTON SQUARE, LONDON, S.W.1. TEL: VICTORIA 0926 10th May, 1940 H. V. Tewson, Esq., Assistant Secretary Trades Union Congress, Transport House, Smith Square, S.W.1 Dear Mr. Tewson, JESUS AND JULIAN HICKMAN URRUTIA Further to our conversation over the telephone this afternoon, I wish to confirm that both the Hickman brothers travel on British Passports, and are British subjects in every respect. They are both willing to accept employment as junior draughtsmen if nothing better can be obtained, but they would like to be engaged together, as otherwise it would be difficult for them to be able to support their family and to move their residence to the place of employment. They further state that, in their belief, the difficulty of language, if it arises at all in draughtsman's work, it is of little importance in their particular job, although they realise that the problem would be quite important in any other job. I need not to say how anxious we are this Delegation are that they should be successful in obtaining suitable employment, and how grateful we should be to you if a situation could be found for our friends. Thanking you once again for everything you are doing on our behalf, Yours sincerely, A. de Gondra Secretary 292/946/27/14